FINANCIAL DETERMINANTS OF PROFIT MANAGEMENT AND PROFITABILITY OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Erna Wati; Handoko Karjantoro; Sari Dewi; Linda Linda (Jurnal Mantik, 2022)
Profitability is a company's ability to create profits at the level of sales. certain assets or shares. The way to see the prospects of a company is usually seen from the development of the company's Earnings Ability. Several factors are considered to affect the profitability of the company such as the ability to earn, the ability of financial structure, non-financial factors, company size and age of the company. From these factors, researchers conducted research on the influence of these five factors on company Earnings Ability. The test results from this study prove that the ability of earnings and company size significantly influence the company's profitability while the ability of financial structure, non-financial factors and company age significantly negatively affect the company's profitability.